2022
DOI: 10.1007/s40670-022-01534-9
|View full text |Cite
|
Sign up to set email alerts
|

A New Normal: Assessment Outcomes and Recommendations for Virtual Versus In-Person Curricula in Post-COVID-19 Times

Abstract: Introduction COVID-19 response efforts that began in March 2020 prompted an urgent need to transition medical education from an in-person to a virtual format. Our aim is to provide evaluation of a virtual platform for a fully integrated curriculum to provide future guidance in teaching methods. Materials and Methods We used summative assessments and course evaluations from pre- and post-transition from in-person to virtual delivery of educational content to measure the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 14 publications
(5 reference statements)
0
3
0
Order By: Relevance
“…The construction of the current VSO program has taken shape. Integrating VSOs more deeply into the curriculum and creating a first-class VSO course will be a new trend in the reform of clinical medicine teaching ( 17 ).…”
Section: Discussionmentioning
confidence: 99%
“…The construction of the current VSO program has taken shape. Integrating VSOs more deeply into the curriculum and creating a first-class VSO course will be a new trend in the reform of clinical medicine teaching ( 17 ).…”
Section: Discussionmentioning
confidence: 99%
“…An important finding in this study was that higher teamwork satisfaction predicted students’ preference for choosing digital SGT in the future (Table 6 ). A recent study suggested that preferences for digital education was relatively low for group learning processes compared to in-person one during the COVID-19 period, especially during prolonged digital learning [ 34 ]. We believe that this phenomenon likely resulted from the suboptimal teamwork satisfaction in under-prepared digital group learning sessions.…”
Section: Discussionmentioning
confidence: 99%
“…First-week online education boomed (Babbar & Gupta, 2022). Data showed students appreciated the setting (Cowan et al, 2022). Learning faded over time.…”
Section: State Of Educationmentioning
confidence: 99%